2012
DOI: 10.1159/000337198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Minimal Change Lesions in Patients with Non-Erosive Reflux Disease: A Case-Control Study

Abstract: Background/Aims: Some minimal changes (MCs) are believed to have a certain relationship with gastroesophageal reflux (GERD). Nonetheless, the individual meaning of MC is still unclear. Our aim was to compare the overall and individual prevalence of MC between patients with non-erosive reflux disease (NERD) and healthy controls (HC). Methods: Twelve endoscopic findings in the esophagogastric junction were prospectively compared between NERD (n = 64) and control (n = 104). Results: Overall frequency of MC (≥1 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In a case–control study, an irregular Z-line has been found with higher frequency in patients with reflux disease19 (Evidence grade IIa). Although one study found that about 40% of cases of irregular Z-line harboured IM on biopsy samples, the significance of this endoscopic finding is still unclear20 (Evidence grade III).…”
Section: Diagnosismentioning
confidence: 95%
“…In a case–control study, an irregular Z-line has been found with higher frequency in patients with reflux disease19 (Evidence grade IIa). Although one study found that about 40% of cases of irregular Z-line harboured IM on biopsy samples, the significance of this endoscopic finding is still unclear20 (Evidence grade III).…”
Section: Diagnosismentioning
confidence: 95%
“…Proposed minimal changes include: vascular changes at the SCJ (vascular spots above the Z-line, punctate erythema/shining of blood vessels through the mucosa, loss of long blood vessels above the Z-line, intraepithelial papillary capillary loop dilation or tortuosity), white mucosal turbidity at the SCJ, irregular Z-line, horizontal erosions, and triangular indentation into the squamous mucosa. 10,[15][16][17][18][19][20][21] Using pH monitoring as the standard, these minimal changes have a sensitivity for the assessment of NERD that ranges from 60% to 90%, and a specificity from 64% to 83%. Despite multiple studies and modalities for the diagnosis of minimal changes, there is no current consensus regarding the definition of "minimal changes.…”
Section: Minimal Changesmentioning
confidence: 99%
“…[3][4][5] Furthermore, an irregular z line is more common in patients with reflux disease. 6 The second catch is noticing an area of columnar metaplasia in the proximal oesophagus and incorrectly labelling this as BE. This is actually a cervical inlet patch and is a developmental abnormality.…”
Section: Recognising What Is Not Be Endoscopic Diagnosismentioning
confidence: 99%